2016
DOI: 10.1186/s13049-016-0262-z
|View full text |Cite
|
Sign up to set email alerts
|

Four ways to ventilate during cardiopulmonary resuscitation in a porcine model: a randomized study

Abstract: BackgroundThe optimal method for out-of-hospital ventilation during cardiopulmonary rescue (CPR) is controversial.The aim of this study was to test different modes of ventilation during CPR for a prolonged period of 60 min.MethodsPigs were randomized to four groups after the induction of ventricular fibrillation, which was followed by one hour of mechanical cardiac compressions. The study comprised five pigs treated with free airways, five pigs treated with ventilators, six pigs treated with a constant oxygen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 24 publications
2
5
0
1
Order By: Relevance
“…Compression only CPR was included in this study for comparison purposes and it was associated with a very low PaO 2 . This value was similar to values reported in pigs after 5–15 min of compression only CPR ( 21 ). Compression only CPR maybe associated with poorer outcomes than conventional CPR in human clinical patients ( 22 24 ).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Compression only CPR was included in this study for comparison purposes and it was associated with a very low PaO 2 . This value was similar to values reported in pigs after 5–15 min of compression only CPR ( 21 ). Compression only CPR maybe associated with poorer outcomes than conventional CPR in human clinical patients ( 22 24 ).…”
Section: Discussionsupporting
confidence: 90%
“…In this study, the animals ventilated via orotracheal intubation developed hypocapnia during CPR, despite a similar degree of ventilation as provided at baseline. This likely reflects the decrease in CO 2 production and reduced blood flow associated with cardiopulmonary arrest and has been reported in previous experimental animal CPR studies ( 21 , 28 30 ). As ventilation was performed manually in this study, we cannot guarantee what tidal volume was provided during the experiment.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Additionally, positive pressure mechanical ventilation causes some alterations in hemodynamic physiology, the most relevant of which is the reduction in venous return and, therefore, the reduction in ventricular preload. 8,9 A recent survey reported that the most commonly used ventilation mode is volume control continuous mandatory ventilation. 10 However, no clinical studies have yet defined the "best" mode of invasive ventilation to use during mechanical CPR.…”
Section: Ventilation Modesmentioning
confidence: 99%
“…From a theoretical point of view, this distinction is essential for determining the risk of atelectasis from oxygen reabsorption; however, from a practical point of view (at least in relation to the studies conducted on animal models), no substantial difference has been identified between the 2 methods in terms of side effects, or between these methods and invasive ventilation performed at zero PEEP. 9,53,54 Although, from a theoretical point of view, the application of PEEP seems to be beneficial for achieving an adequate oxygenation target (see the section on PEEP), other clinical studies have focused on more specifically adapting ventilation to the patient, even during the inspiratory phase. Indeed, avoided an arterial blood pressure drop (P < .001).…”
Section: Hayes Et Al 47mentioning
confidence: 99%